Analisis Green Accounting dan Green Intellectual Capital terhadap Peningkatan Kinerja Keuangan - Budiantini, Alya; Sutihat, Aat; Astuti, Reni (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
In recent years, environmental awareness and the growing importance of intangible assets have encouraged companies to adopt more sustainable practices and focus on value creation beyond physical assets. This research investigates the influence of green accounting and intellectual capital on financial performance, specifically in companies listed in the Consumer Non-Cyclicals and Energy sectors on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Green accounting is measured using the PROPER index, intellectual capital is assessed using the Value Added Intellectual Coefficient (VAIC), and financial performance is measured by Return on Assets (ROA). The study uses a purposive sampling method, resulting in a sample of 14 companies with a total of 70 observations. This quantitative research relies on secondary data and employs panel data regression analysis using EViews 12, with a significance level of 5%. The findings indicate that green accounting does not have a significant effect on financial performance, leading to the rejection of the first hypothesis. However, intellectual capital has a significant positive effect on financial performance, supporting the second hypothesis. These results highlight the growing relevance of intellectual capital in enhancing company performance, while suggesting that environmental initiatives may not yet translate directly into financial returns in the examined sectors.